Dietary restriction suppresses apoptotic cell death, promotes Bcl-2 and Bcl-xl mRNA expression and increases the Bcl-2/Bax protein ratio in the rat cortex after cortical injury. (June 2016) - Lončarević-Vasiljković, Nataša; Milanović, Desanka; Pešić, Vesna; Tešić, Vesna; Brkić, Marjana; Lazić, Divna; Avramović, Vladimir; Kanazir, Selma
Abstract: Traumatic brain injury (TBI) is one of the leading causes of death and disability in humans. Subsequent pathological events occurring in the brain after TBI, referred to as secondary injury, continue to damage surrounding tissue resulting in substantial neuronal loss. Using an animal model of TBI we examined the effect of dietary restriction (DR) on the neuroapoptosis and Bcl-2 family genes as the main regulators of the intrinsic apoptotic pathway. Bcl-2, Bcl-xl and Bax mRNA and protein expression in the ipsilateral cortex of adult Wistar rats exposed to DR before TBI were studied from 2 to 28 days post injury. Our results showed that DR suppressed neuroapoptosis and promoted significant upregulation of antiapoptotic Bcl-2 and Bcl-xl mRNAs in the ipsilateral cortex following injury. Expression of the proapoptotic Bax gene increased in ad libitum (AL) fed rats but remained unchanged in rats exposed to DR. Although the expression of Bcl-2, Bcl-xl and Bax proteins was changed in a similar manner in both experimental groups, DR promoted a continuous increase in the Bcl-2:Bax protein ratio throughout the recovery period. Together with our previous finding that DR mediates inhibition of the extrinsic apoptotic pathway the present work reveals that modulation of the intrinsic pathway contributes to the beneficial effect of DR in brain injury. These findings provide new insight into the effects of DR on pro-survival signaling after injury, lending further support to its neuroprotective effect. Highlights: TBI causes secondary neuronal cell death. DR suppresses neuronal cell death after TBI. DR affects pro-survival signaling after injury.